Development of a framework for obsolescence resolution cost estimation - Romero Rojo, Francisco Javier (Cranfield University, 2011)
Currently, manufacturing organisations worldwide are shifting their business models towards Product-Service Systems (PSS), which implies the development of new support agreements such as availability-based contracts. This transition is shifting the responsibilities for managing and resolving obsolescence issues from the customer to the prime contractor and industry work share partners. This new scenario has triggered a new need to estimate the Non-Recurring Engineering (NRE) cost of resolving obsolescence issues at the bidding stage, so it can be included in the support contract. Hence, the aim of this research is to develop an understanding about all types of obsolescence and develop methodologies for the estimation of NRE costs of hardware (electronic, electrical and electromechanical (EEE) components and materials) obsolescence that can be used at the bidding stage for support contracts in the defence and aerospace sectors. For the accomplishment of this aim, an extensive literature review of the related themes to the research area was carried out. It was found that there is a lack of methodologies for the cost estimation of obsolescence, and also a lack of understanding on the different types of obsolescence such as materials and software obsolescence. A systematic industrial investigation corroborated these findings and revealed the current practice in the UK defence sector for cost estimation at the bidding stage, obsolescence management and obsolescence cost estimation. It facilitated the development of an understanding about obsolescence in hardware and software. Further collaboration with experts from more than 14 organisations enabled the iterative development of the EEEFORCE and M-FORCE frameworks, which can be used at the bidding stage of support contracts to estimate the NRE costs incurred during the contracted period in resolving obsolescence issues in EEE components and materials, respectively. These frameworks were implemented within a prototype software platform that was applied to 13 case studies for expert validation.
Keywords: Obsolescence Management; DMSMS; Product-Service Systems